Simbolis Sosial dalam Lirik Lagu Rumah Kita melalui Analisis Wacana Kritis Model Fairclough - Anisa Puspita Sari; Dewi Kusumaningsih; Pardyatmoko Pardyatmoko; Muhlis Fajar Wicaksana; Suparmin Suparmin (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2026)
This study aims to analyse and elucidate the social symbolic meanings relating to the construction of self-identity and the definition of happiness hidden within the narrative of simplicity in the lyrics of the song Rumah Kita. Employing a descriptive qualitative design, this study applies Norman Fairclough’s Critical Discourse Analysis model through three main dimensions: the textual dimension (microstructural), discourse practices (mesostructural), and sociocultural practices (macrostructural), with data comprising the lyrics of the song Rumah Kita, collected through note-taking from official digital sources. The findings regarding the textual dimension indicate that the use of agrarian vocabulary, rhetorical declarative-interrogative sentences, and the plural personal pronoun “we” strategically transforms physical limitations into identity sovereignty. Furthermore, in the discourse practice dimension, the production and consumption of the text are influenced by the empirical anxieties of urban migrants, thereby making this song a medium for mass cultural resistance. Meanwhile, in the sociocultural practice dimension, the text has the potential to serve as an instrument of counter-hegemony against 1980s capitalism by integrating the Javanese philosophy of nrimo ing pandum. The findings of this research contribute to the development of linguistic studies, particularly Critical Discourse Analysis, by enriching our understanding of how linguistic choices in song lyrics construct identity, representations of happiness, and the ideologies represented through the relationship between textual structure, discursive practices, and sociocultural context.